2017
DOI: 10.17269/cjph.108.6151
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and depression among on-reserve First Nations people in rural Saskatchewan

Abstract: OBJECTIVES:To determine among rural-dwelling on-reserve Saskatchewan First Nations people whether racial discrimination is associated with depression, and in turn, if this relationship is moderated by gender. METHODS:As a component of a community-based participatory research project, a cross-sectional, interviewer-administered survey of 874 adults living on 2 Cree First Nation reserves in rural north-central Saskatchewan was conducted during May-August in 2012 and 2013. Self-reported, health-provider diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In summary, the high prevalence of racism and its association with symptoms of depression adds to previously published research [5,[19][20][21][22][23]. Results were stronger for experiences of racism before age 20 than during the 20s.…”
Section: Modelsupporting
confidence: 57%
See 2 more Smart Citations
“…In summary, the high prevalence of racism and its association with symptoms of depression adds to previously published research [5,[19][20][21][22][23]. Results were stronger for experiences of racism before age 20 than during the 20s.…”
Section: Modelsupporting
confidence: 57%
“…Additionally, the murder of George Floyd served as another wakeup call that racism in America remains a salient and engrained system despite centuries of civil movements for change. Eliminating institutionalized racism is essential for individuals to achieve their maximum health and well-being, but research has also shown the deleterious effects of racism at the interpersonal level on the mental health status of Black people [5,[19][20][21][22][23]. Furthermore, interpersonal/perceived racism defined as unfair treatment experienced by members of marginalized racial and ethnic groups has been identified as a chronic stressor that can have a negative effect on mental and physical health [21,24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Larson et al (2007) stated that physical health was associated with interpersonal racism and cautioned that measures of chronic racism, not acute racism, were more consistently associated with health. A study with a Cree First Nation community showed that interpersonal racism was associated with diagnoses of depression after adjusting for confounders, and the odds of having depression increased with more incidences of interpersonal racism (Janzen et al, 2017). A study in Kettle and Stony Point First Nation, Ontario, determined that perceived stress was positively associated with interpersonal racism, which was modestly impacted by cultural resilience (Spence, Wells, Graham, & George, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some glaring examples include prejudice experienced during the residential school era (Truth and Reconciliation Commission of Canada, 2015b), and more recently the Wet'suwet'en First Nation protests (Bogart, 2020) and Muskrat Falls protests (Samson, 2017), to name only a few. It is also well documented that non-Indigenous individuals can have prejudiced attitudes towards Indigenous individuals (e.g., Morrison et al, 2008;Nesdole, Lepnurm, Noonan, & Voights, 2015), and Indigenous individuals report high levels of experiencing the effects of prejudice (e.g., Godley, 2018;Janzen et al, 2017).…”
Section: Personal Prejudicementioning
confidence: 99%